(3YbO GdJQNjU (B:s (3OQGSI ebGQfI (B= Lease contrac : a comparative study /s - (3GdLHhQ, YdGA YRjR,s 1974- ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2011)
(3cJGH (B"(3YbO GdJQNjU(B... (3OQGSI ebGQfI(B" (3jJejR HNUhUjI JejRg Yf HbjI GdYbhO GdCNQi ShGA Ydi GdUYjO GdfXQj Ch GdYedj GdJWHjbj(B. (3jMed GdcJGH Hjf WjGJg ehVhYGJ egeI hgj Ydi GdJQJjH GdBJj (B: (3eaghe YbO GdJQNjU, hGdJYQja Hg, hJMJ YfhGf (B((3eMd YbO GdJQNjU(B) (3PcQ GdcJGH eaghe HQGAI GdGNJQGY, hGdTQhW GdehVhYjI hGdELQGAGJ GdTcdjI(B. (3hJVef GdcJGH CjVG NUGFU eMd YbO GdJQNjU, hMeGjJg hGdQbGHI Ydi eOi GSJZdGdg, hgj (B: (3GdNUGFU, GdMeGjI, GdQbGHI(B. (3hJMOK GdcJGH CjVG Yf eYWjGJ YbO GdJQNjU, hSeGJg, hJejR YbO GdJQNjU Yf ZjQg ef GdeQGcR GdbGfhfjI, PGcQG CWQGa YbO GdJQNjU, GdeQNU, GdeQNU dg hZjQgG(B. (3hJfGhd GdcJGH eQMdI GdJaGhV GdJegjOjI, hHOA GdeaGhVGJ h VeGfGJgG hJMJ HGH ege hgh (B((3GdCKQ GdbGfhfj ddGJaGbGJ GdChdjI aj eQMdI GdJaGhV(B) (3aQY GdcJGH gPG GdHGH ehVhYGJ YOI, hgj (B: (3GdEHQGe GdfgGFj dYbO GdJQNjU, UjZI YbO GdJQNjU(B.s
(3HHdjhLQGajI (B: (3UaMI (B249-256.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdYbhO (B((3bGfhf eOfj(B)s; (3GdJQGNjUs -- (3bhGfjf hJTQjYGJs; (3GdELQGAGJ GdEOGQjIs -- (3bhGfjf hJTQjYGJs